Strontium and calcium contents of bone density fractions. - Triffitt, J; Sutton, A (Springer-Verlag, 1969)
The Sr/Ca ration in bone is approximately the same as in serum, whereas hydroxyapatite powders suspended in physiological solutions discriminate against strontium. It was found that the Sr/Ca ratio of various density fractions of powdered compact bone of rat tibia increased with increasing density to a value slightly higher than that observed in the serum. The explanation could be that a cellular barrier removes calcium preferentially to strontium from the bone fluid, or that early accentuation of the bone Sr/Ca ration is reflected in the higher density fractions. © 1969 Springer-Verlag.